Wiatr od Morza . no. 1, 1981 - "Solidarność" Sekcja Oświaty i Wychowania, [ed. Bronisława Piasecka et al.] ([s.n.], 1981)
Creation and circulation: After introduction of the Martial Law publication suspended. Republished in 1988